Analisis Perhitungan Cost-Volume-Profit (CVP) Sebagai Dasar Perencanaan Laba Pada UMKM Obot Fried Chicken - Guruh Ardana; Endah Dwi Kusumastuti; Anny Suryani (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The COVID-19 pandemic has affected all aspects of life, including the economy. In Indonesia, the most affected by the COVID-19 pandemic are MSMEs. The limited activities that can be carried out lead to reduced sales. Even in the midst of limited conditions, as an MSME, of course, you want to get optimal profits. This study aims to determine the selling price of the product that should be and the number of products that must be sold in order to get the expected profit on Obot Fried Chicken SMEs by using analysis cost-volume-profit. The type of research used is descriptive using analytical tools such as Contribution Margin, Break-even point, Operational Leverage, Margin of Safety, Profit Planning Analysis and Selling Price Determination at Obot Fried Chicken SMEs. The results of this study indicate that the selling price set is right to achieve the profit target of 30%. With a profit target of 30%, UMKM Obot Fried Chicken must be able to target product sales of 14.557 pcs with a sales target in rupiah of Rp.87.341.090